BIOGRAFI PROF. dr. TABRANI RAB TAHUN 1941-2015 - Zahri, Rezi Yuni; Tugiman, Tugiman; Asril, Asril (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Biography is the story of a character's life journey written by someone else based on information from the character or other sources. In this case, the author raised the biography of a Riau community figure, Prof. dr. Tabrani Rab. The purpose of this study is 1) to describe the biography of Prof. dr. Tabrani Rab, 2) to describe the role of Prof. dr. Tabrani Rab in the field of education, 3) to describe the role of Prof. dr. Tabrani Rab in the field of politics, 4) to describe the role of Prof. dr. Tabrani Rab in the field of socio-cultural, 5) to describe the role of Prof. dr. Tabrani Rab in the field of health, 6) to describe the role of Prof. dr. Tabrani Rab in the field of economics and the world of the press, 7) to describe the works made by Prof. dr. Tabrani Rab. The method used in this research is descriptive qualitative method. The data collection techniques in the form of interview, literature and documentation. The results of this study can be concluded that Prof. dr. Tabrani Rab was born in Bagansiapi-api, Rokan Hilir on September 30, 1941. He had many roles. In the field of education by building educational institutions and providing scholarships to students. In the field of politics as the President of the Free Riau Movement. In the field of health as a doctor, he established a hospital. In the filed of socio-cultural together with Al-Azhar and Soeman HS founded the Riau Cultural Institute. In the field of economics by attending present in various meetings such as Asiaâ€™s Role in The Changing World, International Conference, Taipe-Taiwan 1992 and Tokyo-Japan and in the world of the press with Prof. Drs. Suwardi MS and Soeman HS founded the Genta newspaper. Then, he also actively wrote one of them â€Tempiasâ€ which is published every Sunday in Riau Pos. He published many works in the form of books, one of which was the book â€Towards a Sovereign Riau: The Choice of the Riau People's Congress II which discussed Riau Merdekaâ€.Key Words: Biography, Tabrani Rab.